The Role of Employee Regrouping and Expertise Outsourcing as Intervening Variables in the Relationship of the Crisis Period: Lessons Learned from the Suralaya Power Generation Unit - Idrus, Irwan; Suseno, Bambang Dwi; Adiguna, Leistar; Firjatullah, Solida; Sukapatanaa, Chintara (MIX: JURNAL ILMIAH MANAJEMEN, 2025)
Objectives: This study investigates the effects of crisis management, particularly in the context of the COVID-19 pandemic, on expertise outsourcing and production efficiency at PLTU Suralaya.It explores how the pandemic reshaped employee regrouping and outsourcing practices to maintain operational continuity. While outsourcing specialized expertise is increasingly common, limited empirical evidence exists on its effectiveness during crises. Poorly managed outsourcing can lead to inefficiencies, increased costs, and reduced productivity. The study assesses optimal integration between in-house teams and outsourcing partners, evaluating selection criteria, collaboration effectiveness, and crisis resilience strategies.Methodology: This study's use of the entire population of PT. Indonesia Power Suralaya’s Generation Division ensures data accuracy, eliminates sampling bias, and enhances the reliability of findings. This method enables a thorough examination of internal dynamics, ensuring that the findings are more relevant and tailored to the organization's unique context.Findings: Statistical analysis revealed significant positive effects of the pandemic on employee productivity (path coefficient: 0.320), employee regrouping (0.500), and expertise outsourcing (0.448). Both regrouping and outsourcing positively influenced productivity, highlighting their crucial role in crisis management.Conclusion: To enhance productivity, companies should adopt strategic regrouping and outsourcing processes, ensuring Human Resources professionals are equipped with the right skills, resources, and technology. These findings offer actionable insights for navigating crises and ensuring operational resilience. This research contributes to the understanding of crisis management, outsourcing, and employee productivity, emphasizing their strategic role in sustaining business continuity and efficiency during disruptions.